Isolation, characterization and antibacterial activity of actinomycetes from soils of the Langun-Gobingob Cave Complex in Calbiga, Samar - Damayo, Jeffrae Isaac Albert R.; Fuentes, Rolly G. (Annals of Tropical Research, 2021)
The discovery of rare Actinomycetes from unexplored areas has proven to be a promising source of new antimicrobials. The Langun-Gobingob cave complex in Calbiga, Samar, Philippines is the second largest cave complex in Asia, yet this is the first reported search for actinomycetes conducted in the area. The main objective of this study was to assess the antibacterial activities of culturable actinomycetes from soil samples from the Langun-Gobingob cave complex. Five actinomycete colonies were isolated in pure culture from soil samples using Starch-Casein Agar medium. The isolates were identified by their morphological characteristics and they were characterized by 16S rRNA sequencing. The sequences were matched to sequences uploaded to the NCBI Basic Local Alignment Search Tool (BLAST). Four of the isolates belonged to the Genus Streptomyces and one belonged to the Genus Nocardia. The antibacterial potential of the isolates was tested against gram-positive and gram-negative test bacteria. One Streptomyces isolate exhibited antibacterial activity against the two gram-positive test bacteria. The limited cave area sampled in this study leaves the cave complex mostly unexplored in the search for antibacterial secondary metabolites.